Professional learning community (PLC): approach to enhance students' achievement in language learning at public university, Malaysia - Othman, Shamsudin; Jamian, Abdul Rasid; Md Sabil, Azhar; Said, Rozita @ Radhiah; Omar, Rosmaria (Horizon Research Publishing, 2020)
Professional Learning Community (PLC) is a form of self-development for educators which has been known internationally and currently through the phase of implementation in Malaysia. Purpose of this study was focused on PLC implementation that had been applied widely in Higher Education Institution (HEI) which; 1) to identify the relationship between educators' comprehension, readiness and strategies for language learning, and 2) to form a predictive model of relationship between educator's knowledge, preparation and strategy toward improving student's language learning. Three dimensions of PLC which comprehension, readiness and strategies in PLC were analyzed by using SPSS and AMOS. Three hundred sixty students and five lecturers involved as respondents. Correlation analysis and structured equation modeling were used to answer the research objectives. Qualitative data as The predictive model achieved a good fit value of RMSEA=.055, GFI=.980, CFI=.981, TLI=.983 and Chisq/df=2.164. Interview data of 5 educators showed that decency was the main key theme in improving student language learning achievement. The implementation of PLC that related to language as well decency learning had given a new approach in teaching, particularly for educators and students in a language course. The predictive model can be used as primary source guidelines in elevating the Malay language at a higher level, especially for next researches. Secondary source supported the findings. Results showed that there were significant values derived from the relationship between comprehension and language learning (r=.401, p=.000), the relationship between readiness and language learning (r=.541, p=.000), and the relationship between strategy and language learning (r=.891, p=.000).